Some neural and hemato-immune factors correlated with lysozime saliva level in children living on territories polluted by radionucleides - T S Seniv; R A Seniv; I S Flyunt; M R Uhryn; W Zukow (Kazimierz Wielki University, 2015)
Seniv T S, Seniv R A, Flyunt I S, Uhryn M R, Zukow W. Some neural and hemato-immune factors correlated with lysozime saliva level in children living on territories polluted by radionucleides. Journal of Education, Health and Sport. 2015;5(5):275-282. ISSN 2391-8306. DOI 10.5281/zenodo.17737 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A275-282 https://pbn.nauka.gov.pl/works/560515 http://dx.doi.org/10.5281/zenodo.17737 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015.   SOME NEURAL AND HEMATO-IMMUNE FACTORS CORRELATED WITH LYSOZIME SALIVA LEVEL IN CHILDREN LIVING ON TERRITORIES POLLUTED BY RADIONUCLEIDES   T S Seniv1, R A Seniv1, I S Flyunt2, M R Uhryn2, W Zukow3   1Clinical Sanatorium "Moldova", Truskavets', Ukraine san_moldova@mail.ru 2Faculty of Physical Education Ivan Franko University, Drohobych, Ukraine 3Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland   Summary Objective. We know that children who live on territories polluted by radionucleides, characterized, among other things, increased prevalence diseases to caries and periodontitis. On the other hand, for the rest of this contingent characterized by dysfunction of the neuroendocrine-immune complex. We set a goal to find out the relationships saliva lysozyme activity - a key factor in antibacterial protection of the oral cavity - with some blood-neural and immune factors. Methods. The study involved 80 children aged 10-17 years, who arrived to the spa Truskavets' from territories polluted by radionucleides. In addition to the activity of lysozyme in saliva, recorded parameters of immune status I-II levels of WHO, HRV, Stange and Hench tests, and conducted routine clinical tests. Results. Normal activity of saliva lysozyme pronounced only in 17 (21%) children. Regarding immunity parameters detected significant positive correlation activity of lysozyme with the intensity (r=0,49) and activity (r=0,34) phagocytosis by neutrophils blood Staph. aureus and concentration of serum IgM (r=0,34) and circulating immune complexes (r=0,30), whereas a negative correlation with the levels of IgA (r=-0,46), CD19+ B lymphocytes (r=-0,32) theophilinsensitive T lymphocytes (r=-0,26) and CD8+ T lymphocytes (r=-0,23). Among the HRV parameters with the activity of lysozyme only weakly correlated markers vagal tone RMSSD (r=-0,19) i PSD HF (r=-0,19). The observed negative correlation lysozyme activity of inspiratory test Stange (r=-0,47) and expiratory test Hench (r=-0,27). Among hemogram parameters significantly correlated with the activity of lysozyme only platelet level (r=-0,22). The canonical correlation between saliva lysozyme activity and registered blood-neural and immune factors proved strong (R=0,82). Conclusion. Reduced activity of lysozyme in saliva of children, who live on territories polluted by radionucleides, is one of the manifestations of dysfunction neuroendocrine-immune complex.   Keywords: saliva lysozyme, immunity, HRV, Stange and Hench tests, children.